2012
DOI: 10.1161/circulationaha.112.120410
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Necrosis Factor-α Therapy Reduces Aortic Inflammation and Stiffness in Patients With Rheumatoid Arthritis

Abstract: Background— Rheumatoid arthritis (RA) is a systemic inflammatory condition associated with increased cardiovascular risk. This is not fully explained by traditional risk factors, but direct vascular inflammation and aortic stiffening may play a role. We hypothesized that patients with RA exhibit aortic inflammation, which can be reversed with anti-tumor necrosis factor-α therapy and correlates with aortic stiffness reduction. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 44 publications
12
133
0
6
Order By: Relevance
“…These findings may help to explain why antirheumatic therapies, including anti‐TNF treatment, decrease the risk of CVD 7. In theory, these therapies may reduce the CV risk not only due to an effect on systemic inflammation but also due to a direct effect on the vasculature: both on inflammation in plaques, and on adventitial inflammation, which is suspected to be involved in both atheroma formation and destabilization.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings may help to explain why antirheumatic therapies, including anti‐TNF treatment, decrease the risk of CVD 7. In theory, these therapies may reduce the CV risk not only due to an effect on systemic inflammation but also due to a direct effect on the vasculature: both on inflammation in plaques, and on adventitial inflammation, which is suspected to be involved in both atheroma formation and destabilization.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with this notion, current research has indicated a reduction in CV morbidity or mortality in patients who are treated effectively with antirheumatic therapies, which might be at least partially mediated through inhibition of vascular inflammation. In support of this concept, a recent study demonstrated significant attenuation of vascular inflammation in RA patients who received anti‐TNF therapy 7. Thus, with the introduction of new immunologic therapies, it is essential to examine which immune factors are involved in the vascular inflammatory process, because this may have implications for prevention and treatment of CVD.…”
mentioning
confidence: 99%
“…Mizoguchi and colleagues [38] used FDG to demonstrate a reduction in vascular inflammation with pioglitazone. Similarly, in an investigation of vascular inflammation in rheumatoid arthritis, 8 weeks of anti-TNFa therapy reduced aortic FDG uptake in addition to showing the expected benefits in terms of general disease activity [34].…”
Section: Imaging Inflammation Using Fdg Petmentioning
confidence: 93%
“…In carotid imaging, high FDG uptake correlates well with features of vulnerability noted on other modalities, for example, echolucency on ultrasound [30] and lipid rich cores on MRI [31]. Vascular FDG PET is being used to investigate the excess cardiovascular risk associated with other chronic inflammatory diseases such as HIV [32], chronic obstructive pulmonary disease [33] and rheumatoid arthritis [34].…”
Section: Imaging Inflammation Using Fdg Petmentioning
confidence: 99%
“…При-менение традиционных базисных противовоспалительных препаратов (БПВП), в частности метотрексата (МТ), а так-же генно-инженерных биологических препаратов (ГИБП), таких как ингибиторы фактора некроза опухоли α (ФНОα), связано со значительным снижением риска ССЗ у пациен-тов с РА [35,38,40,[42][43][44][45]. В пилотных исследованиях по-казано, что снижение активности РА коррелирует с сурро-гатными маркерами риска развития ССЗ: уменьшением толщины комплекса интима-медиа на фоне терапии тоци-лизумабом или ритуксимабом (РТМ) [46][47][48]; улучшением артериальной ригидности и жесткости аорты на фоне лече-ния МТ и ингибиторами ФНОα [49][50][51][52].…”
Section: рекомендация 1 для снижения риска ссз необходим эффективныйunclassified